(3GdTchc Ydi cdGe CaVd GdCWHGA LGdjfhS aj GdcJH GdJj fSHJ Edjgs - (3eMeO Hf RcQjG GdnqQGRj, CHh HcQ,J (B311 (3g` s
(3ChdgG (B:s
(3bGd eMeO Hf RcQjG GdQGRi (B: (3Efi dCYde cKjQkG ef GfGS jSJLgdhffi aj JCdja gPG GdcJGH hcKjQkG efge jdheffi hjTgO Gddg Cf gPg GdTchc GdJj PcQgG aj gPG GdcJGH de Jcf aj cJH gPG GdQLd GdMHQ GdaGVd (B((3LGdjfhS(B) s
(3BNQgG (B:s
(3ajfXQ GdBf aj gPG GdcJGH HYjf YOd , aef jYfjg GdMb hjMH GdYde dfaSg hjLYd KhGH YfGFfG Hg eWGdYJg HeG Tc ajg efg , hGdMeO dhGgH GdYbd , hdi GdYOd hGdMce hGdaVd MeOkG HdG fgGjI s
(3Vef eLehY , JQJjHgG (B: (3ef U (B150 - (3U(B185s
(3GfXQg eY HSJGf GdWHGA Qbe (B" 349 - 351"s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B143 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs